2012
DOI: 10.1186/2046-9063-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Yarrowia lipolytica biofilms by rhamnolipid biosurfactant

Abstract: BackgroundYarrowia lipolytica is an ascomycetous dimorphic fungus that exhibits biofilm mode of growth. Earlier work has shown that biosurfactants such as rhamnolipids are efficient dispersants of bacterial biofilms. However, their effectiveness against fungal biofilms (particularly Y. lipolytica) has not been investigated. The aim of this study was to determine the effect of rhamnolipid on a biofilm forming strain of Y. lipolytica. Two chemical surfactants, cetyl-trimethyl ammonium bromide (CTAB) and sodium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…It has been previously demonstrated that the use of biosurfactants preventively, that is, prophylactically, can prevent the formation of fungal biofilms (Dusane et al . ).…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
“…It has been previously demonstrated that the use of biosurfactants preventively, that is, prophylactically, can prevent the formation of fungal biofilms (Dusane et al . ).…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
“…Rhamnolipids have also been shown to be effective dispersal agents for fungi disrupting pre-formed biofilms of Yarrowia lipolytica on glass surfaces by ≈67 % which was more effective in comparison to the surfactants cetyl-trimethyl ammonium bromide (CTAB) and sodium dodecyl sulphate (SDS) (Dusane et al 2012).…”
Section: Rhamnolipidsmentioning
confidence: 99%
“…Other glycolipids as antibiofilm molecules Dusane et al (2012) reported that a glycolipid based on glucose and palmitic acid produced by a tropical marine Cells were stained with Syto9® and observed using a fluorescence microscope at 40×. The bar represents 100 μm.…”
Section: Sophorolipidsmentioning
confidence: 99%
“…This biosurfactant showed efficacy as an antimicrobial and antibiofilm agent for a wide spectrum of pathogens, including orally related microorganisms. Dusane et al (2012) investigated the effect of rhamnolipids on Yarrowia lipolytica biofilm formation on different surfaces, where rhamnolipids caused an inhibition of Y. lipolytica biofilm production on plastic and glass by 50% and 67%, respectively. The report does not provide insight into the chemical composition of the rhamnolipids used.…”
Section: Potential Biosurfactant Applications For Oral Health and Hygmentioning
confidence: 99%